Study of microleakage in dental enamel using nanofillers composite resin restoration with total-etch and self-etch adhesive - Iin Sundari; Viona Diansari; Niska Darlianti (Dentistry Faculty, 2020)
Microleakage is a poor marginal adaptation of the restoration, often found between cavity and restoration material. One of the reasons is the shrinkage during the composite resin during polymerization, causing the restorations adaption disturbed. Application of adhesive material on the cavity affects microleakage at the margin restoration and increases the adaptation between cavity and restoration material. This research aims to determine microleakage in dental enamel using nanofiller composite resin restoration with fifth-generation total-etch adhesive and eight-generation self-etch adhesive. This research used 16 specimens premolars, which were prepared cavity Class I G.V. Black and divided into two groups (group A and B). Group A used nanofiller composite resin FiltekTM Z350 + fifth-generation total-etch Adper Single Bond 2 (n=8), group B used nanofiller composite resin Filtek TM Z350 + eight-generation self-etch Universal Single Bond Adper (n=8). The specimen isolated using nail polish except in the work area.,then immersed in methylene blue 1% at 25C (for 24 hours). After that, all specimens were washed and cut longitudinally. The results were observed using a Stereomicroscope and Scanning Electron Microscope (SEM). The observations results showed that the amount number of microleakage in group A (75%) less than in group B (100%), while the non-parametric statistic test using the Mann Whitney showed no significant differences (p0.143). Based on SEM images, the average distance between enamel and composite resin with total-etch adhesive was 1.40 0.007m, and 1.84 0.509 m for resin composite with self-etch adhesive. This research concluded that microleakage using nanofiller composite with the fifth-generation total-etch adhesive was smaller than nanofiller composite resin with the eighth -generation self-etch adhesive.KEYWORDS: Adhesive system, nanofillers composite resin, microleakage, enamel